Trastornos de conducta y su relación con trastornos depresivos y de ansiedad en adolescentes privados de la libertad en el Centro de Atención Integral de Adolescentes Infractores de Loja. - Samaniego Namicela, Luis Guillermo (2017)
The present research wanted to establish the existence of a relationship between behavioral disorder, depressive disorder, and anxiety disorder in adolescents deprived of their freedom in the “Centro de Atención Integral de Adolescentes infractores de Loja”. A retrospective study was carried out in adolescents from July to December 2016. These days were selected by probabilistic sampling. In the development of the research, the Clinical History was created, which allowed us to know that 83.3% of patients in the sample present behavioral alterations such as: intangible and physical violence, substance use, and emotional tension. The application of the Goldberg test to adolescents deprived of freedom in the “Centro de Atención Integral de Adolescentes infractores de Loja” showed that the adolescents studied presented depression in 83.3% and anxiety in 76.6%. With this background it is concluded that the behavioral disorders and other characteristics of this type of alterations are related to anxiety and depression. Key words: Adolescents, Depression, Anxiety, Behavioral disorder